Immunogenic cell death-inducing chemotherapeutic nanoformulations potentiate combination chemoimmunotherapy - Jianhua Liu; Zhongmin Li; Duoyi Zhao; Xiangru Feng; Chunxi Wang; Di Li; Jianxun Ding (Materials & Design, 2021)
Chemotherapeutic nanoformulations, which can induce the immunogenic death of tumor cells, have attracted increasing attention for their abilities to enable and potentiate combination chemoimmunotherapy. Immunogenic cell death (ICD) causes the release of tumor-associated antigens, tumor-specific antigens, danger-associated molecular patterns, and pro-inflammatory cytokines, which trigger adaptive immune cells to elicit an antitumor immune response. The combination of ICD-inducing nanomedicines and immunoactivators represents a promising strategy for enhancing chemoimmunotherapy in clinical applications. In this review, we provide an overview of the latest advances in chemotherapeutic nanoformulation-mediated immune activation and the combination strategies with various immunoactivating agents, such as immune checkpoint inhibitors, indoleamine 2,3-dioxygenase inhibitors, cytokines, and Toll-like receptor agonists, and predict their potential to contribute significantly to clinical cancer chemoimmunotherapy.